Real and Money Wage Rates: Further Comment - Tarshis, Lorie (Quarterly Journal of Economics, 1941)
Further Comment Get access Lorie Tarshis Lorie Tarshis National Bureau of Economic Research Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 55, Issue 4, August 1941, Pages 691–697, https://doi.org/10.2307/1884125 Published: 01 August 1941